2022
DOI: 10.11591/ijai.v11.i1.pp276-283
|View full text |Cite
|
Sign up to set email alerts
|

Model optimisation of class imbalanced learning using ensemble classifier on over-sampling data

Abstract: <span lang="EN-US">Data imbalance is one of the problems in the application of machine learning and data mining. Often this data imbalance occurs in the most essential and needed case entities. Two approaches to overcome this problem are the data level approach and the algorithm approach. This study aims to get the best model using the pap smear dataset that combined data levels with an algorithmic approach to solve data imbalanced. The laboratory data mostly have few data and imbalance. Almost in every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Salah satu Teknik untuk mengurangi kelas tidak seimbang digunakan Teknik data sampling yang dapat membagi kelas mayoritas menjadi kelas yang seimbang [10]. Teknik data sampling berhasil meningkatkan akurasi yang dihaslkan Ensemble Classifier [11], Teknik data sampling dapat mengatisipasi data kelas yang tidak seimbang [12] Selain data sampling untuk meningkatkan nilai akurasi dari klasifikasi adalah metode pemilihan fitur dengan memilih subset fitur yang dipilih dari jumlah dataset [13], seleksi fitur adalah proses dimana Sebagian ruang fitur dipilih sesuai relevansinya dengan mempertimbangkan keluaran dari klasifikasi [14]. PSO merupakan algoritma Optimasi fitur dapat meningkatkan nilai akurasi yang dihasilkan PSO telah digunakan untuk optimasi peningkatan akurasi untuk Random forest, decision tree, naïve bayes dan KKN untuk klasifikasi dataset diabetes [15].…”
Section: Latar Belakangunclassified
“…Salah satu Teknik untuk mengurangi kelas tidak seimbang digunakan Teknik data sampling yang dapat membagi kelas mayoritas menjadi kelas yang seimbang [10]. Teknik data sampling berhasil meningkatkan akurasi yang dihaslkan Ensemble Classifier [11], Teknik data sampling dapat mengatisipasi data kelas yang tidak seimbang [12] Selain data sampling untuk meningkatkan nilai akurasi dari klasifikasi adalah metode pemilihan fitur dengan memilih subset fitur yang dipilih dari jumlah dataset [13], seleksi fitur adalah proses dimana Sebagian ruang fitur dipilih sesuai relevansinya dengan mempertimbangkan keluaran dari klasifikasi [14]. PSO merupakan algoritma Optimasi fitur dapat meningkatkan nilai akurasi yang dihasilkan PSO telah digunakan untuk optimasi peningkatan akurasi untuk Random forest, decision tree, naïve bayes dan KKN untuk klasifikasi dataset diabetes [15].…”
Section: Latar Belakangunclassified
“…Moreover, [17] observed that the Adaboost method could be applied to improve classifier performance. In addition, [18], [19], and [20] also conducted experiments by assessing comparisons among SMOTE, Adaboost, and bagging techniques to increase the accuracy level of a prediction.…”
Section: Introductionmentioning
confidence: 99%